PENGARUH BRAND IMAGE DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN ULANG DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MODERATING : THE INFLUENCE OF BRAND IMAGE AND SERVICE QUALITY ON REPURCHASE DECISIONS WITH CUSTOMER SATISFACTION AS MODERATING VARIABLES (Jurnal Riset Manajemen dan Akuntansi, 2022)
The purpose of this study was to determine and analyze the effect of brand image and service quality on repurchase decisions with consumer satisfaction as a moderating variable. This research was conducted on the Shopee marketplace with respondents residing in the Greater Jakarta area. This research category is using descriptive method and causality. The sampling technique used purposive sampling with a total sample of 420 respondents. Collecting data using a questionnaire. The data analysis technique uses Structural Equation Modeling (SEM) analysis which is processed with Smart PLS 3.0. The results of the study prove that brand image has a significant effect on repurchase decisions in the Shopee marketplace. Service quality has a significant effect on repurchase decisions on the Shopee marketplace. Consumer satisfaction did not succeed in moderating the relationship between brand image and repurchase decisions. Consumer satisfaction managed to moderate the relationship between service quality and repurchase decisions.